PENERAPAN MODEL PEMBELAJARAN QUANTUM LEARNING PADA MATERI LISTRIK DINAMIS UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA KELAS XII SMA NEGERI 8 INDRAGIRI HULU - Rahmadani, Ririn; Maaruf, Zuhdi; Islami, Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to describe the self directed learning of students in physics through the application of Quantum Learning model on the dynamic electricity subject. This type of research is pre-experiment research using one group pre-test post-test design. The participants are the students of XII class SMAN 8 Indragiri Hulu with the number of 24 people. The pre-exeriment research instrument use self directed learning ability questionnaires. Descriptive analysis technique is used as data analysis technique. The results showed that the initial level of self directed learning ability of the students was at score 2.60 and after application of Quantum Learning model was at score 2.70. This study concludes that the Quantum Learning model increase the independence of physics learning on the dynamic electricity subject.Keywords : Quantum Learning, Self Directed Learning Ability, Dynamic Electricity